APPLICATION OF STABLE ISOTOPE FORENSICS FOR PREDICTING REGION OF ORIGIN OF HUMAN REMAINS FROM PAST WARS AND CONFLICTS. Issue 1 (May 2014) - Bartelink, Eric J.; Berg, Gregory E.; Beasley, Melanie M.; Chesson, Lesley A.; Kimmerle, Erin H.
<x xml:space="preserve">Abstract</x> The application of stable isotope analysis has provided novel approaches for provenancing unidentified human remains from forensic contexts. Stable isotope ratios measured in human tissues provide a record of the foods consumed during life as well as the geographic location where drinking water or food was obtained. This study begins with an overview of the application of stable isotope analysis for provenancing human remains, followed by three cases that illustrate how chemical signatures in bone reflect a probable region of origin. Using stable carbon and nitrogen isotopes of human bone, we test whether human skeletal remains recovered by the Joint POW/MIA Accounting Command‐Central Identification Laboratory (JPAC‐CIL, or CIL) reflect a geographic origin within North America or Asia. Stable carbon and nitrogen isotopes of human bone collagen and stable carbon isotopes of bone apatite reflect consumption of food resources that are expected to vary between world regions due to cultural dietary differences. Based on the isotopic differences, a testable hypothesis of geographic origin can be applied, determining if the remains are more likely of a U.S. service person or of an indigenous local. We believe that this approach can provide useful information for narrowing search parameters in unidentified persons cases; can contribute to human rights cases where an unknown individual is thought to originate from a different geographic area; and, in human remains cases of unknown geographic provenience, can determine whether a person is local or nonlocal.